2013
DOI: 10.1111/cla.12058
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of features of the female reproductive system and other morphological characters in leeches (Citellata, Hirudinida) in phylogenetic conception

Abstract: An epistemological–evolutionary conception of leeches (Hirudinida) based on features of the female reproductive system in combination with other morphological characters is presented in the spirit of the cladistic school of taxonomy. Characters relating to the structure of the ovary and the course of oogenesis in leeches were interpreted in this manner, for the first time. Each study was conducted on type species of higher taxonomic groups of true leeches. Results of analyses using features of the reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In this context, knowledge about characters connected with organization of female gonads and oogenesis may provide new and potentially useful traits that can be used in phylogenetic considerations of Clitellata. Such characters were recently used by Bielecki et al (2014) to analyze leech phylogeny, and they were found to reflect well the phylogenetic relationships of Hirudinida at the family level.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, knowledge about characters connected with organization of female gonads and oogenesis may provide new and potentially useful traits that can be used in phylogenetic considerations of Clitellata. Such characters were recently used by Bielecki et al (2014) to analyze leech phylogeny, and they were found to reflect well the phylogenetic relationships of Hirudinida at the family level.…”
Section: Introductionmentioning
confidence: 99%
“…The organization of the female germ-line cysts in such taxa as clitellate annelids, nematodes and mites is more complicated; the center of the cyst is occupied by an anuclear cytoplasmic mass (cytoplasmic core, central core) of a different shape and size, which is called a cytophore in clitellate annelids, a gonad core or a rachis in nematodes and a medulla in mites, while the germ cells are located at the periphery of the cyst. Additionally, as a rule, each germ cell is connected to the cytoplasmic core via only one stable intercellular bridge [ 21 – 32 ]. The number of germ cells in cysts that have a central core is usually high (the lowest known number is 16 in the white worm, Enchytraeus albidus [ 33 ]) and usually varies between taxa and may even vary between different germ-cell clusters in the same ovary (e.g., there are from 24 to 44 cells in fish leeches, Piscicola [ 34 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the gross morphology of the female germ-cell cysts in some clitellate annelids has been described in several taxa e.g., in leeches [ 26 , 28 ], and in oligochaetous clitellates [ 27 , 31 ]. These studies revealed that there is a great deal of variety in the cyst morphology in these animals (for more details see Discussion , [ 32 ] and references herein). One of the groups of Clitellata in which germ-line clusters have drawn special attention due to their complicated form is Tubificinae.…”
Section: Introductionmentioning
confidence: 99%
“…The same features of the apical cell have been found in E. octoculata and E. johanssoni (Świątek et al, ; Ben Ahmed et al, ). The apical cell was also found in all of the hirudinids and haemopids that have been studied to date (see Table ) and should be regarded as an apomorphy of arhynchobdellid leeches (Bielecki et al, ). It was suggested that the apical cell plays active role in maintaining germ and somatic stem cells (Ben Ahmed et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…The sperm ultrastructure has been frequently used in phylogenetic analyses (e.g., Ferraguti and Erséus, ; Jamieson, ; Marotta et al, ; Marotta and Ferraguti, ). Similarly, some morphological (Brinkhurst, ; Brinkhurst and Gelder, ; Siddall and Burreson, ) and recently also the ultrastructural (Bielecki et al, , ; Cichocka et al, ) characters of the female reproductive system and oogenesis have also been used in the phylogenetic assessment of Clitellata. The organization of female gonads and some details about oogenesis have also successfully been used to shed more light on the phylogeny of the other animals such as, for example, arthropods (Štys and Biliński, ; Büning, ; Mayer and Tait, ; Kubrakiewicz et al, ; Tworzydło et al, ).…”
Section: Introductionmentioning
confidence: 99%